Optimalisasi Komposisi Koktail dan Pengembangan Proses Fermentasi Up-scale dari Empat Strain Bakteri Komensal Kulit - Ahmad Baikuni; Meidy Richky Wanyodiharjo; Harry Ardiansyah; Fathan Luthfi Hawari; Amarila Malik (Fakultas Farmasi Universitas Pancasila, 2022)
Analyzing the actual microbial composition in the skin microbiome is riveting to create a potential sourceof active substances in skincare products. Our previous study isolated four bacterial strains from Javanese male and female skin samples, Staphylococcus hominis MBF12–19J, Staphylococcus warneri MBF02–19J, Bacillus subtilis MBF10–19J, and Micrococcus luteus MBF05–19J. This study aimed to determine the composition of those strains in a bacterial cocktail and optimize the condition for up-scale laboratory production of the cocktail. To assess the ability of bacteria to coexist and live in cocktail communities, simultaneous monitoring was performed using the Deferred Growth Inhibition Assay (DGIA) method and real-time PCR for DNA copy number measurement. Results showed the best composition based on even distribution and cell growth viability was at the ratio 1.5:1:0.5:0.5 of Micrococcus luteus MBF05-19J, Bacillus subtilis MBF10-19J, Staphylococcus warneri MBF02-19J, Staphylococcus hominis MBF12-19J, which is equivalent to DNA copy number/mL 1.209 x 1024 CFU : 2.484 x 1041 CFU : 2.645 x 1041 CFU : 9.041 x 1035 CFU, respectively. The optimum growth incubation time of individual bacterial cultures for an up-scale 2-L bio-fermentor mixture was as follows; Micrococcus luteus MBF05-19J = 21 hrs; Bacillus subtilis MBF10-19J = 7 hrs; Staphylococcus warneri MBF02-19J = 17 hrs; Staphylococcus hominis MBF12-19 = 15 hrs. For up-scale conditions, the fermentation incubation time was 3 hours at 37oC, agitation 50 RPM, and aeration 5% dissolved oxygen.